CXCR3 and CXCR5 are highly expressed in HIV‐1‐specific CD8 central memory T cells from infected patients. Issue 8 (7th June 2021) - Olivo, Anaëlle; Lécuroux, Camille; Bitu, Marie; Avettand‐Fenoel, Véronique; Boufassa, Faroudy; Essat, Asma; Meyer, Laurence; Doisne, Jean‐Marc; Favier, Benoit; Vaslin, Bruno; Schlecht‐Louf, Géraldine; Noël, Nicolas; et al.
Abstract: New ways of characterizing CD8 + memory T cell responses in chronic infections are based on the measurement of chemokine receptor expression (CXCR3, CXCR5, and CX3CR1). We applied these novel phenotyping strategies to chronic HIV infection by comparing healthy donors (HDs), HIV‐infected patients receiving antiretroviral therapy (ART), and spontaneous HIV controllers (HICs). In all groups, the memory cells exhibited high proportion of CXCR3 + cells. Proportions of CXCR5 + and CX3CR1 + cells were preferentially observed among central memory cells (Tcm) and effector memory cells (Tem) respectively. Chronic controlled HIV infection impacted the chemokine receptor profile of both HIV‐specific and nonspecific CD8 + T cells. In total CD8 + T cells, the proportions of CXCR3 – CXCR5 – CX3CR1 – Tcm and Tem were lower in HIV‐infected patients than in HDs with subtle differences between ART and HICs. Such phenotyping strategy also revealed differences in exhaustion and senescence phenotypes, the CXCR3 + CXCR5 + CX3CR1 – being more exhausted and senescent than the CXCR3 + CXCR5 – CX3CR1 – Tcm fraction. Among HIV‐specific CD8 + T cells, the vast majority of Tcm cells were CXCR3 + and CXCR5 + cells in contrast with their nonspecific counterparts. In conclusion, the addition of migration markers contributes to better characterize Tcm/Tem compartment. Abstract : CXCR3 is constitutively expressed on CD8 + memory T cells. CXCR5 and CX3CR1 are preferentially expressed by central and effector CD8 + memory T cells respectively, although in low proportions. HIV‐specific central CD8 + memory T cells exhibit higher proportions of CXCR3, CXCR5, and CX3CR1 expressing cells than their nonspecific counterpart.